Effects of Intratesticular Lidocaine in Pet Rabbits Undergoing Orchiectomy - Matteo Serpieri; Giuseppe Bonaffini; Chiara Ottino; Giuseppe Quaranta; Mitzy Mauthe von Degerfeld (Animals, 2024)
The use of local anesthetics for castration is both simple and cost-effective, and it may contribute to reducing the anesthetic requirements. Despite its common use in clinical practice, the literature regarding the effects of intratesticular lidocaine in rabbits is limited. In this study, nine rabbits per group were assigned to intratesticularly receive either 2% lidocaine (0.05 mL/kg into each testicle) or an equivalent volume of saline prior to elective orchiectomy. Anesthesia was induced by intranasal administration of ketamine, medetomidine, and butorphanol. During intraoperative assessment, no significant differences in vital parameters (heart rate, respiratory rate, and peripheral saturation of oxygen) were observed between the groups. However, rabbits receiving intratesticular saline displayed a higher incidence of responses to surgical stimuli. Postoperative pain was evaluated using the composite Centro Animali Non Convenzionali Rabbit Scale (CANCRS), revealing a significantly lower score at the initial post-surgery assessment in rabbits treated with intratesticular lidocaine. All subjects exhibited rapid resumption of food intake and fecal output. While all rabbits demonstrated satisfactory perioperative performances, the use of intratesticular lidocaine was associated with a diminished response to surgical stimuli. Consequently, this practice has the potential to reduce the requirement for additional anesthetics or analgesics, promoting faster recovery.